Method of analysing the risk of injury in young female gymnasts due to repetitive loading and fatigue - Beatty, K. T. (2007)
The majority of gymnasts are young girls. Training hours required to meet competition demands are high and gymnasts begin serious training at a young age. Concerns regarding injury risk are substantial and may be the result of repeated high impact loads experienced during landings from dismounts, tumbling and vaulting. There is currently little information available to coaches regarding the quantity of training that is safe or not safe. The use of acceleration was tested for its efficacy for use in the field to examine risk factors for injury. Risk factors examined were loading and fatigue. Kinematics, ground reaction forces and acceleration were measured during landing from gymnastics skills and also pre- and post fatigue during landing from a vertical jump and a 35cm drop in the laboratory. A pilot study was performed in the field to examine accelerations during gymnastics skills pre- and post-training. Lower body kinematics of landing were notably different between gymnastics skills analysed. Joint positions at touchdown and range of motion available during landing due to these joint positions affect the ability to contribute to energy absorption. Peak ground reaction forces and peak accelerations measured at the pelvis showed significant differences between skills landing on both the hands and the feet. The peak acceleration during landing from gymnastics skills was positively correlated with the peak ground reaction force. A large variability stiffness during landing meant that an estimation of ground reaction force using simple modelling was not successful in improving the correlation. After a fatiguing jumping and landing task peak accelerations measured at the pelvis during landing were increased indicating the use of acceleration for identifying fatigue. Pilot field testing of acceleration during landing from gymnastics skills showed similar results to laboratory results. Pre- and post-training measurements showed no difference in peak accelerations during landing from the skills analysed. The training session completed was not demanding enough to induce enough fatigue to be seen in acceleration values Acceleration has potential to be used to quantify repeated loading and accumulative effects in gymnastics, as well as the presence of fatigue in gymnasts during training sessions.